Conjugation-mediated genetic exchange in Legionella pneumophila. - Dreyfus, L A (1985)
Genetic exchange mechanisms, to our knowledge, have not been reported for Legionella pneumophila, and consequently, studies on the genetic organization of L. pneumophila have not appeared in the literature. Here, we describe gene transfer mediated by broad host range conjugative plasmids in Legionella spp. Escherichia coli strains carrying plasmids RP1 and R68.45 (IncP1), S-a (IncW), and R40a (IncC), but not plasmids of incompatibility groups FI, FII, and FV, served as donors in matings with L. pneumophila Knoxville 1 (LPK-1). Transconjugants selected by resistance to kanamycin (RP1, R68.45, and S-a) and carbenicillin (R40a) were observed at frequencies of 6.6 X 10(-3), 4.7 X 10(-3), 2.2 X 10(-4), and 5.4 X 10(-5), respectively. Plasmid transfer was not affected by DNase added to the mating medium. After plasmid transfer, LPK-1 stably maintained RP1, R68.45, and S-a, but not R40a. Plasmid-containing LPK-1 isolates also served as donors in agar plate matings with E. coli W1485-1 and naladixic acid-resistant mutants of LPK-1, Legionella micdadei, and Legionella longbeachii. Recombinational exchange of a chromosomal trait was demonstrated when a thymidine auxotroph of L. pneumophila was repaired by R68.45-mediated chromosomal mobilization of a prototrophic donor strain.